(untitled) (GYMNASIUM, 2020)
The interdependence between cognitive and motor skills development, and also the experience we gained teaching in classes I-IV, influenced our decision to accomplish this study. Thus we have seen that the cognitive and motor development can be optimized using methods and means of physical education, both those from the physical education curriculum and other methods studied by various specialists. The study on cognitive and motor skills of students in grades I-IV was conducted over three stages over a period of six weeks. The cognitive and motor skills are very important for the child development. These two branches are interrelated and influence each other. Therefore we need a very good systematic physical education lessons, taking into account the psychomotor, affective and cognitive objectives.